2017
DOI: 10.1136/vr.103996
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial isolates and antimicrobial susceptibilities from odontogenic abscesses in rabbits: 48 cases

Abstract: The medical record database of a veterinary teaching hospital was searched from 2000 through 2014 for records of client-owned rabbits with positive cultures from odontogenic abscesses. Data reviewed included sex, age, abscess location, sampling technique, previous antimicrobial treatments, microorganisms identified and antibiotic susceptibility of aerobic bacteria. Forty-eight client owned rabbits with one or more odontogenic abscesses and culture results were evaluated. One hundred and eighty-five isolates (5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 24 publications
0
28
0
1
Order By: Relevance
“…Bacteria isolated from odontogenic abscesses from rabbits (Tyrrell and others 2002, Jekl and others 2012, Gardhouse and others 2015) and guinea pigs (present study) are sensitive to penicillins and clindamycin; however, these drugs can cause clostridial infections and toxaemia, and cannot be used in guinea pigs. Odontogenic abscesses in guinea pigs were, apart from surgical debridement, treated medically with marbofloxacin (Capello and Lennox 2012), enrofloxacin or metronidazole (Souza and others 2006).…”
Section: Discussionmentioning
confidence: 51%
“…Bacteria isolated from odontogenic abscesses from rabbits (Tyrrell and others 2002, Jekl and others 2012, Gardhouse and others 2015) and guinea pigs (present study) are sensitive to penicillins and clindamycin; however, these drugs can cause clostridial infections and toxaemia, and cannot be used in guinea pigs. Odontogenic abscesses in guinea pigs were, apart from surgical debridement, treated medically with marbofloxacin (Capello and Lennox 2012), enrofloxacin or metronidazole (Souza and others 2006).…”
Section: Discussionmentioning
confidence: 51%
“…is known to be one of the most common bacteria causing abscesses in rabbits. [21]. Our investigation found that five of the Pseudomonas spp.…”
Section: Resultsmentioning
confidence: 80%
“…Rabbits have long been used as laboratory models for human gingivitis and periodontal disease studies. Anaerobic bacteria play an important role in infections and abscess formation [21]. Periapical infections and abscesses in rabbits and rodents caused by P. multocida have been reported [27,30].…”
Section: Discussionmentioning
confidence: 99%
“…A combination of medical and surgical treatment is considered the treatment of choice as it has a higher rate of success. In one study, the most common organisms detected in odontogenic abscesses were anaerobic bacteria, such as Fusobacterium species, followed by Peptostreptococcus species, Bacteroides species, and aerobic bacteria such as P aeruginosa , Pasteurella species, Streptococcus species, Staphylococcus species (Gardhouse and others 2017). Choice of surgical technique (eg, removal of the entire abscess or marsupialisation) depends on the location and severity of the abscess.…”
Section: Common Dermatological Conditionsmentioning
confidence: 99%
“…For culture and sensitivity testing, a sample of both capsule and pus should be taken; pus alone can sometimes be sterile. Antibiotics such as penicillin G (40 mg/kg given subcutatneously every 24 hours), metronidazole (20 mg/kg given orally every 12 hours or 40 mg/kg given orally every 24 hours) and enrofloxacin (20 mg/kg given orally or subcutaneously every 24 hours) proved to be effective in most cases and could be started while awaiting the bacteriology results (Tyrrell and others 2002, Taylor and others 2010, Gardhouse and others 2017). Radiographic examination and computed tomography can be useful to assess whether the infection has involved the underlying bone and soft tissues.…”
Section: Common Dermatological Conditionsmentioning
confidence: 99%